A Crane Robot of Three Axes Dimensional Using Trajectory Planning Method - Triyanto Pangaribowo; Muhammad Hafizd Ibnu Hajar; Julpri Andika; Adi Juliyanto (International Journal of Advanced Technology, 2020)
This study aims to design a crane robot that has good performance with good stability, good accuracy in the gripper clamping the object at the point of balance and reach the target location well. The crane controller is installed with US-100 ping sensor and proximity infrared sensor to detect position of object. The robot crane moves on the x , y and z axes or in three  dimensions using motors as actuator and  it can be adjusted with motor drive. The crane moves on the x and y axes using  DC motor and z axis using servo motor. The crane automatically moves when it detects an object. The crane's movement uses the trajectory determination method by maintaining speed. Finally, the average accuracy of the gripper clamping exactly at the midpoint of the object is 93%. The length of the object when it is clamped has an accuracy of 95%. The performance of the crane robot is evaluated to transfer an object to the destination location takes 11 seconds with a track length of 86.055 cm